Low dielectric constant polymer substrate and its manufacturing method
The ion beam pretreatment of polymer substrates for flexible copper-clad laminates improves adhesion with metal or ceramic coatings, addressing peeling issues and maintaining thinness and flexibility, suitable for high-speed communication devices.
Patent Information
- Application Number
- JP2024534419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-09
- Filing Date
- 2021-12-10
- Publication Date
- 2024-12-17
AI Technical Summary
Conventional flexible copper-clad laminates face issues with adhesion between polymer substrates and metal or ceramic coatings, leading to peeling during high-temperature processes and increased thickness, which hinders flexibility and bending resistance, and existing surface treatments for polymers with low dielectric constants like fluorine-containing materials do not effectively enhance adhesion.
A low dielectric constant polymer substrate is manufactured with a surface modified layer formed by ion beam pretreatment, allowing direct deposition of metal or ceramic coatings without an adhesive layer, using gases like hydrogen, helium, or argon to improve adhesion, and employing ion beam assisted sputtering deposition to form the coating layer.
The method enhances adhesion between the polymer and metal or ceramic layers, reduces manufacturing complexity, and maintains a thin profile while ensuring flexibility and durability, suitable for high-speed communication devices.
Smart Images

Figure 2024546117000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a low dielectric constant polymer substrate and a manufacturing method thereof, and more particularly, to a low dielectric constant polymer substrate capable of depositing a metal or ceramic with high adhesion without a separate adhesive layer by modifying the surface of the polymer substrate, and a manufacturing method thereof. [Background technology]
[0002] Recently, as the demand for electronic products to have higher performance, faster transmission speeds, smaller size, lighter weight and thinner profile has increased, interest has been growing in materials such as flexible printed circuit boards (FPCBs), which are a major component of FPCBs, as well as flexible copper clad laminated substrates (FCCLs), which are a core material for FPCBs.
[0003] Flexible copper clad laminates are made by laminating copper foil on one or both sides of a polymer film, and are excellent in terms of flexibility such as flex resistance. Conventional flexible copper clad laminates are made by forming a metal layer such as nickel, chromium, titanium, etc. on a polymer substrate and then depositing copper to improve adhesion with the metal. Flexible copper clad laminates require a separate etching process when forming patterns in the future, but flexible copper clad laminates with the above structure have the problem that the polymer film can peel off from the metal layer and copper deposition layer during high temperature processes. In addition, there is a problem that the thickness of the flexible copper clad laminate, which is important for flexibility and flex resistance, increases.
[0004] In addition to the demand and trends for electronic products, low dielectric constant materials with low signal loss are important in the 5G and beyond communications market, which requires high-speed transmission of large amounts of data in high-frequency bands. As a result, development of polymer substrates with low dielectric constants that can be applied to communications devices such as flexible copper-clad laminates and ultra-high-speed communication antennas, server boards, etc., is ongoing.
[0005] In particular, among low dielectric constant polymers, fluorine-containing polymers generally have low adhesive strength to a polymer substrate even when a metal thin film is formed on the polymer substrate due to its hydrophobic nature. Therefore, in order to improve adhesive strength with a thin film formed on the polymer substrate, a method of pretreating the surface of the polymer substrate with ultraviolet light or the like has been attempted, but it is difficult to obtain a significant improvement in adhesive strength, and there is a problem in that the applicability is limited.
[0006] Therefore, there is a need to develop a low dielectric constant polymer substrate that has a low dielectric constant, a smaller thickness, and excellent adhesion to a coating layer.
[0007] As background art of the present invention, Japanese Patent Registration No. 6076844 describes a surface treatment method for fluorine-containing resin and a surface treatment device for fluorine-containing resin. Summary of the Invention [Problem to be solved by the invention]
[0008] It is an object of the present invention to provide a low dielectric constant polymeric substrate having improved adhesion between a polymeric layer and a metal or ceramic coating layer.
[0009] Another object of the present invention is to provide a method for efficiently manufacturing a low dielectric constant polymer substrate having improved adhesion between a polymer layer and a metal layer.
[0010] It is still another object of the present invention to provide a method for manufacturing a low dielectric constant polymer substrate with a reduced manufacturing process.
[0011] Other objects and advantages of the present invention will become apparent from the following detailed description, claims and drawings. [Means for solving the problem]
[0012] According to one embodiment, there is provided a low dielectric constant polymer substrate comprising a low dielectric constant polymer layer, a surface modification layer formed on the surface of the polymer layer by pretreatment with an ion beam, and optionally a metal or ceramic coating layer formed on the surface modification layer, wherein the contact angle of the surface modification layer with water is 90° or less.
[0013] According to an embodiment, the low dielectric constant polymer layer may include at least one of polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP).
[0014] According to an embodiment, the low dielectric constant polymer layer may have a dielectric constant of 4 or less. According to an embodiment, the low dielectric constant polymer layer may have a thickness of 0.01 mm or more and less than 2 mm. According to an embodiment, the ion beam pretreatment may be an ion beam pretreatment in which hydrogen gas, helium gas, or argon gas and hydrogen gas are used.
[0015] According to an embodiment, the metal may be one or more of Cu, Ni, Cr and Ti.
[0016] According to an embodiment, the ceramic may be at least one of ZnO and ITO (Indium tin oxide).
[0017] According to another aspect, an article of manufacture is provided that includes the low dielectric constant polymeric substrate described herein.
[0018] According to yet another aspect, there is provided a method for manufacturing a low dielectric constant polymer substrate, comprising the steps of pretreating a surface of a low dielectric constant polymer layer with an ion beam for surface modification, and selectively forming a metal or ceramic coating layer on the polymer layer, wherein the ion beam energy during the ion beam pretreatment is 50 to 2000 eV.
[0019] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present application, the low dielectric constant polymer layer may include at least one of polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP).
[0020] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present application, the gas used for the ion beam pretreatment may be hydrogen gas, helium gas, or argon gas and hydrogen gas.
[0021] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present application, when the gas used in the ion beam pretreatment is hydrogen, the applied power per ion beam velocity may be 2 kW / mpm or less.
[0022] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present invention, when the thickness of the low dielectric constant polymer layer is 0.01 to less than 2 mm, the applied voltage during the ion beam pretreatment may be 0.5 to less than 2 kV.
[0023] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present invention, the metal or ceramic coating layer may be formed by sputtering deposition or ion beam assisted sputtering deposition.
[0024] According to an embodiment, in the method of manufacturing a low dielectric constant polymer substrate of the present invention, the above steps may be performed in a roll-to-roll process.
[0025] According to an embodiment, in the method for manufacturing a low dielectric constant polymer substrate of the present application, the process speed of the roll-to-roll process may be 0.1 to 10 mpm. Effect of the Invention
[0026] According to an embodiment, a low dielectric constant polymer substrate having excellent adhesion between a polymer layer and a metal or ceramic coating layer can be provided by controlling ion beam pretreatment conditions.
[0027] According to an embodiment, a low dielectric constant polymer substrate having excellent adhesion between a polymer layer and a metal or ceramic coating layer can be efficiently manufactured by controlling ion beam pretreatment conditions.
[0028] According to an embodiment, a low dielectric constant polymer substrate can be manufactured by shortening the manufacturing process through ion beam pretreatment without the need for a separate adhesive layer forming process. [Brief description of the drawings]
[0029] [Figure 1] 1 is a schematic diagram illustrating a low dielectric constant polymer substrate according to an embodiment of the present invention. [Diagram 2]1A to 1C are diagrams illustrating a method for manufacturing a low dielectric constant polymer substrate according to a first embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram illustrating a method for producing a low dielectric constant polymer substrate according to Comparative Examples 1 to 3 of the present invention. [Figure 4] 10 is a diagram illustrating a schematic diagram of a method for producing a low dielectric constant polymer substrate according to Comparative Example 4 of the present invention. [Diagram 5] 4 is a graph showing a contact angle of water on a low dielectric constant polymer substrate having a surface modification layer formed thereon according to an embodiment of the present invention. [Figure 6] 1 is an image showing a surface shape according to an embodiment of the present invention as a function of the amount of applied power per velocity of a hydrogen gas ion beam. [Figure 7] 4 is a graph showing a result of analyzing surface components of a low dielectric constant polymer substrate having a surface modification layer formed thereon according to an embodiment of the present invention. [Figure 8] 1 is an image showing a surface structure of a metal layer of a low dielectric constant polymer substrate according to an embodiment of the present invention. [Figure 9] 1 is a graph showing the results of an adhesion test of a low dielectric constant polymer substrate according to an embodiment of the present invention. [Figure 10] 1 is an image showing a cross cut test result of a low dielectric constant polymer substrate according to an embodiment of the present invention. [Figure 11] 2 is a diagram illustrating a 90° peeling test method for a low dielectric constant polymer substrate according to an embodiment of the present invention; FIG. [Figure 12] 1 is an image showing a result of a 90° Peeling test of a low dielectric constant polymer substrate according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The terms used in this application are merely used to describe particular embodiments and are not intended to limit the present invention.
[0031] A singular expression includes a plural expression unless the context clearly indicates otherwise.
[0032] In this application, terms such as "comprise" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof set forth in the specification, and should be understood as not precluding the possibility of the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0033] In this application, when a part "includes" a certain element, this does not mean excluding other elements, but means that it may further include other elements, unless otherwise specified to the contrary. In addition, throughout the specification, "on" means being located above or below the target part, and does not necessarily mean being located on the upper side based on the direction of gravity.
[0034] Since the present invention can be modified in various ways and can have various embodiments, specific embodiments will be illustrated in the drawings and described in detail in the detailed description. However, it should be understood that this is not intended to limit the present invention to a specific embodiment, and includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention. In describing the present invention, if a detailed description of related publicly known technology is deemed to obscure the gist of the present invention, the detailed description will be omitted.
[0035] Terms such as first, second, etc. may be used to describe various components, but the components should not be limited by the terms. The terms are used only to distinguish one component from another.
[0036] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the description with reference to the accompanying drawings, the same or corresponding components will be given the same drawing numbers, and duplicate descriptions thereof will be omitted.
[0037] FIG. 1 is a schematic diagram showing a low dielectric constant polymer substrate of the present invention.
[0038] Referring to FIG. 1, one embodiment of the present invention provides a low dielectric constant polymer substrate comprising a low dielectric constant polymer layer 10, a surface modification layer 12 formed on the surface of the polymer layer 10 by pre-treating the surface of the polymer layer 10 with an ion beam, and optionally a metal or ceramic coating layer 20 formed on the surface modification layer 12, wherein the surface modification layer 12 has a contact angle with water of 90° or less.
[0039] The low dielectric constant polymer layer 10 may be made of various known materials, including, but not limited to, at least one of polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP).
[0040] Although not limited thereto, the dielectric constant of the low dielectric constant polymer layer 10 may be equal to or less than 4. According to the above-mentioned configuration, the durability is excellent and the signal loss rate is minimized, and the low dielectric constant polymer layer 10 can be effectively applied to communication devices such as antennas for ultra-high speed communication, server boards, displays, etc.
[0041] Although not limited thereto, the thickness of the low dielectric constant polymer layer 10 may be 0.01 mm or more and less than 2 mm. According to the above-mentioned configuration, the low dielectric constant polymer layer 10 has excellent flexibility and bending resistance as well as excellent durability, and can be usefully applied to flexible copper-clad laminates, communication devices such as ultra-high speed communication antennas, server boards, displays, etc.
[0042] The surface modified layer 12 is formed by ion beam pretreatment. The ion beam pretreatment modifies the surface of the polymer layer 10, and the adhesion to the metal or ceramic coating layer 20 can be improved without a separate adhesive layer. When the surface is modified by the ion beam pretreatment, the surface energy is increased, and the contact angle with water can be reduced. Without being limited thereto, the surface modification layer 12 having a water contact angle of 90° or less may be suitable for the bonding surface between the polymer layer 10 and the metal or ceramic coating layer 20, the surface modification layer 12 having a water contact angle of 80° or less may be more suitable, the surface modification layer 12 having a water contact angle of 70° or less may be more suitable, the surface modification layer 12 having a water contact angle of 60° or less may be more suitable, the surface modification layer 12 having a water contact angle of 50° or less may be more suitable, the surface modification layer 12 having a water contact angle of 40° or less may be more suitable, the surface modification layer 12 having a water contact angle of 30° or less may be more suitable, the surface modification layer 12 having a water contact angle of 20° or less may be more suitable, the surface modification layer 12 having a water contact angle of 10° or less may be more suitable, and the surface modification layer 12 having a water contact angle of less than 10° may be more suitable.
[0043] Although not limited thereto, the ion beam pretreatment may be an ion beam pretreatment using hydrogen gas, helium gas, or argon gas and hydrogen gas. According to the above configuration, it is suitable for improving the adhesion between the polymer layer 10 and the metal or ceramic coating layer 20, and the ion beam pretreatment using argon gas and hydrogen gas is more suitable.
[0044] The metal may be, but is not limited to, one or more of Cu, Ni, Cr and Ti.
[0045] The ceramic may be at least one of ZnO and ITO (Indium tin oxide), but is not limited thereto.
[0046] Although not limited thereto, the metal or ceramic coating layer 20 may be formed on both sides of the polymer layer 10 .
[0047] Without being limited thereto, the metallic or ceramic coating layer 20 may be a single layer or multiple layers.
[0048] According to another aspect, an article of manufacture is provided that includes the low dielectric constant polymeric substrate described herein.
[0049] The product may be a product that requires flexibility, bending resistance, low dielectric constant, etc. The product may be one of the following, but is not limited to: a flexible copper-clad laminate, a communication antenna, a communication device, a server board, and a display.
[0050] According to yet another aspect, there is provided a method for manufacturing a low dielectric constant polymer substrate, comprising: performing an ion beam pretreatment on a surface of a low dielectric constant polymer layer for surface modification; and optionally forming a metal or ceramic coating layer on the polymer layer, wherein the ion beam energy during the ion beam pretreatment is 50 to 2000 eV.
[0051] The ion beam pretreatment step is a step of modifying the surface of the low dielectric constant polymer layer to increase adhesion with the coating layer. At this time, the ion beam energy is preferably 50 to 2000 eV to increase the surface energy and increase adhesion between the polymer layer and the metal or ceramic coating layer, more preferably 50 to 1500 eV, even more preferably 50 to 1000 eV, and even more preferably 50 to 500 eV.
[0052] Although not limited thereto, if the ion beam energy is less than 50 eV, the surface modification effect may be insufficient, and if it exceeds 2000 eV, the polymer layer may be deformed, and the adhesion with the metal or ceramic coating layer may be reduced.
[0053] In the method for manufacturing a low dielectric constant polymer substrate of the present application, the low dielectric constant polymer layer may include, but is not limited to, one or more of polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP).
[0054] In the method for manufacturing a low dielectric constant polymer substrate according to the present application, the gas used in the ion beam pretreatment may be, but is not limited to, hydrogen gas, helium gas, or argon gas and hydrogen gas. This configuration is suitable for improving the adhesion between the polymer layer and the metal or ceramic coating layer, and is more suitable for using argon gas and hydrogen gas, and is even more suitable for performing the ion beam pretreatment using argon gas and then performing the ion beam treatment using hydrogen gas.
[0055] Although not limited thereto, in the method for manufacturing a low dielectric constant polymer substrate of the present application, when the gas used in the ion beam pretreatment is hydrogen, the applied power per ion beam velocity is suitable for increasing the adhesion between the polymer layer and the metal or ceramic coating layer to be 2 kW / mpm or less, and more suitable is 1.7 kW / mpm or less.
[0056] In the method for manufacturing a low dielectric constant polymer substrate according to the present invention, when the gas used in the ion beam pretreatment is argon and hydrogen, the total applied power per speed of the argon ion beam and the hydrogen ion beam is 3 kW / mpm or less, which is suitable for maintaining the surface shape of the low dielectric constant polymer layer and improving the adhesion with the coating layer, and is more suitable for being 2.5 kW / mpm or less.
[0057] In the method for manufacturing a low dielectric constant polymer substrate of the present application, when the thickness of the low dielectric constant polymer layer is 0.01 to less than 2 mm, the applied voltage during the ion beam pretreatment may be 0.5 to less than 5 kV, more preferably 0.5 to less than 2 kV, in terms of improving adhesion and preventing deformation of the polymer layer, but is not limited thereto. When the thickness of the low dielectric constant polymer layer is relatively thin, if the applied voltage is out of the range of 0.5 to less than 5 kV, the adhesion may decrease or the polymer layer may be deformed.
[0058] Next, in the method for manufacturing a low dielectric constant polymer substrate of the present application, the step of forming a metal or ceramic coating layer on the polymer layer may be, but is not limited to, formed by sputtering deposition or ion beam assisted sputtering deposition. When the metal or ceramic coating layer is formed by ion beam assisted sputtering deposition, the coating layer may be formed more densely, improving physical properties, and the adhesion between the polymer layer and the coating layer may also be improved.
[0059] Although not limited thereto, in the method for manufacturing a low dielectric constant polymer substrate of the present application, the above steps may be performed by a roll-to-roll process. When the roll-to-roll process is used, there is an advantage that a large area of low dielectric constant polymer substrates can be mass-produced. Although not limited thereto, the process speed of the roll-to-roll process may be preferably 0.1 to 10 mpm.
[0060] Working Example The present invention will be described in more detail below with reference to specific examples and comparative examples of the present invention and the results of evaluation of their characteristics.
[0061] 1. Evaluation of adhesion between low-k polymer layer and copper coating layer with and without ion beam pretreatment Example 1 FIG. 2 is a diagram illustrating a method for manufacturing a low dielectric constant polymer substrate according to a first embodiment of the present invention.
[0062] The surface of 2 mm-thick low dielectric constant polymer PTFE was pretreated with a linear ion beam at 1.2 kV and a speed of 1 mm / s using Ar gas, and a 300 nm-thick Cu layer was deposited on the ion beam pretreated PTFE by DC sputtering with a power of 400 W to produce the low dielectric constant polymer substrate of Example 1.
[0063] Then, in order to evaluate the adhesion between the PTFE substrate and the Cu layer of the low dielectric constant polymer substrate of Example 1, a 10 μm Cu layer was plated on the evaporated Cu layer, and the adhesion was evaluated using a 90° Peeling Tester. As a result, it was confirmed that the adhesion between the PTFE substrate and the Cu layer was 6 N / cm.
[0064] Comparative Example 1 to Comparative Example 3 FIG. 3 is a diagram illustrating a schematic diagram of a method for producing a low dielectric constant polymer substrate according to Comparative Examples 1 to 3 of the present invention.
[0065] The surface of 2 mm thick low dielectric constant polymer PTFE was pretreated with a linear ion beam at 1.2 kV and 1 mm / s using Ar gas, and a 100 nm thick Ti layer (Comparative Example 1), Cr layer (Comparative Example 2), and NiCr layer (Comparative Example 3) were deposited as adhesive layers on the ion beam pretreated PTFE by DC sputtering at a power of 300 W. A 300 nm thick Cu layer was deposited on the PTFE on which the Ti layer (Comparative Example 1), Cr layer (Comparative Example 2), and NiCr layer (Comparative Example 3) had been deposited by DC sputtering at a power of 400 W, thereby producing low dielectric constant polymer substrates of Comparative Examples 1 to 3.
[0066] Thereafter, in order to evaluate the adhesion between the PTFE substrate and the Cu layer of the low dielectric constant polymer substrates of Comparative Examples 1 to 3, a 10 μm Cu layer was plated on the deposited Cu layer, and the adhesion was evaluated using a 90° Peeling Tester. As a result, it was confirmed that the adhesion between the PTFE substrate and the Cu layer in Comparative Example 1 was 0.4 N / cm, that in Comparative Example 2 was 0.5 N / cm, and that in Comparative Example 3 was 3.6 N / cm.
[0067] Comparative Example 4 FIG. 4 is a diagram illustrating a method for producing a low dielectric constant polymer substrate according to Comparative Example 4 of the present invention.
[0068] Comparative Example 4 was manufactured by depositing a 300 nm thick Cu layer on a 2 mm thick PTFE surface, which is a low dielectric constant polymer, by DC sputtering at a power of 400 W without carrying out an ion beam pretreatment process.
[0069] Thereafter, in order to evaluate the adhesion between the PTFE substrate and the Cu layer of the low dielectric constant polymer substrate of Comparative Example 4, a 10 μm thick Cu layer was plated on the deposited Cu layer, and the adhesion was evaluated using a 90° Peeling Tester. As a result, it was confirmed that the adhesion between the PTFE substrate and the Cu layer was 0.1 N / cm.
[0070] According to the above adhesion evaluation results, it can be seen that when the metal coating layer is deposited after the ion beam pretreatment on the surface of the low dielectric constant polymer layer, the adhesion between the low dielectric constant polymer layer and the metal coating layer is better than when the ion beam pretreatment is not performed or when the metal coating layer is deposited after the adhesive layer is formed.
[0071] Therefore, the low dielectric constant substrate of the present invention can improve the adhesion between the low dielectric constant polymer layer and the coating layer without forming a separate adhesive layer, and can also shorten the manufacturing process.
[0072] 2. Evaluation of water contact angle of low-k polymer layer pretreated with ion beam according to gas type Low dielectric constant polymer PTFE, FEP, and PFA substrates were prepared, and ion beam pretreatment was carried out under the following conditions using different types of gas on the surface of each polymer substrate to form a surface modified layer, and the water contact angle of the polymer substrate surface on which the surface modified layer was formed was measured. The energy of the ion beam used to form the surface modified layer is distributed in the range of 30% to 80% of the ion beam anode voltage and generally has a Gaussian distribution shape, so an ion beam anode voltage of 0.6 to 1.2 kV was used to irradiate the specimen with an ion beam having an energy level of 300 to 1000 eV.
[0073] 1) Argon (Ar) - 1 kV, 70 mA, 0.6 mpm, 10 times, 1.17kW / mpm 2) Oxygen (02) - 1 kV, 58 mA, 0.1 mpm, 2 times, 1.16 kW / mpm 3) Hydrogen (H2) - 1 kV, 80 mA, 0.1 mpm, 2 times, 1.6 kW / mpm 4) Argon (Ar) and Hydrogen (H2) - Argon (Ar): 0.6kV, 26 mA, 0.1 mpm, 2 times, 0.31 kW / mpm - Hydrogen (H2): 1.2kV, 80mA, 0.1mpm, 2 times, 1.92kW / mpm - 2.23 kW / mpm total FIG. 5 is a graph showing a water contact angle of a low dielectric constant polymer substrate having a surface modification layer formed thereon according to an embodiment of the present invention.
[0074] 5, the contact angles of water on the surfaces of PTFE, FEP and PFA substrates treated with hydrogen ion beams were all 50° or less, and the contact angles of water on the surfaces of PTFE, FEP and PFA substrates treated with hydrogen ion beams after argon ion beam treatment were all 10° or less. This shows that the contact angles of water are significantly lower than those of argon ion beam treatment or oxygen ion beam treatment. A significantly lower contact angle of water means that the surface energy is high, which indicates that the surface shape of the polymer layer pretreated with ion beams is less changed.
[0075] FIG. 6 is an image showing a surface shape according to the applied power amount per velocity of a hydrogen gas ion beam according to one embodiment of the present invention.
[0076] 6, when the applied power per velocity of the hydrogen gas ion beam is 2.1 kW / mpm or more, the surface shape of the low dielectric constant polymer substrate changes. Therefore, it was confirmed that the applied power per velocity of the ion beam during hydrogen ion beam pretreatment is suitable to be 2.0 kW / mpm or less.
[0077] Therefore, it has been confirmed that the low dielectric constant polymer substrate of the present application, which can be applied to flexible copper-clad laminates and the like, can be suitable for being treated with a hydrogen ion beam to maintain a flat surface shape, and that treatment with an argon ion beam followed by a hydrogen ion beam can be suitable for maintaining a flat surface shape.
[0078] 3. Component analysis results of low-dielectric constant polymer layer surface pretreated with ion beam according to gas type PTFE substrates, a low dielectric constant polymer, were prepared, and ion beam pretreatment was performed on the surface of each PTFE substrate using different gases to form a surface modification layer.Then, X-ray photoelectron spectroscopy (XPS) was used to analyze the components of the polymer substrate surface on which the surface modification layer was formed.
[0079] FIG. 7 is a graph showing a result of analyzing surface components of a low dielectric constant polymer substrate having a surface modification layer formed thereon according to an embodiment of the present invention.
[0080] 7, when the PTFE surface was not pretreated with an ion beam and when it was pretreated with an oxygen ion beam, a peak was present at a binding energy of 292 eV corresponding to the C-F bond of the fluoropolymer. On the other hand, when the PTFE surface was pretreated with a hydrogen ion beam or with argon and a hydrogen ion beam, almost no peak appeared near the binding energy of 292 eV corresponding to the C-F bond. In other words, when the PTFE surface was pretreated with a hydrogen ion beam or with argon and a hydrogen ion beam, the peak near the binding energy of 292 eV corresponding to the C-F bond was 3×10 4 It was below CPS.
[0081] Therefore, it was confirmed that the contact angle with water can be reduced and the adhesion to the coating layer can be improved by pretreating the surface of the fluoropolymer with a hydrogen ion beam or a combination of argon and hydrogen ion beam and selectively removing fluorine.
[0082] 4. Low-dielectric constant polymer substrate with a metal coating layer deposited after ion beam pretreatment according to the gas type FIG. 8 is an image showing a surface structure of a metal layer of a low dielectric constant polymer substrate according to an embodiment of the present invention.
[0083] 8, it can be seen that when copper is deposited on the hydrogen ion beam-treated PTFE, FEP, and PFA substrates after hydrogen ion beam treatment, the surface structure is flat, whereas when copper is deposited on the oxygen ion beam-treated PTFE, FEP, and PFA substrates after oxygen ion beam treatment, the surface structure is not flat, with protruding structures being formed.
[0084] Therefore, it has been confirmed that the low dielectric constant polymer substrate of the present application, which can be applied to flexible copper-clad laminates, etc., can be treated with a hydrogen ion beam to maintain a flat surface shape, and can be treated with an argon ion beam followed by a hydrogen ion beam to maintain a flat surface shape.
[0085] 5. Evaluation of adhesion strength of low-dielectric constant polymer substrates on which metal coating layers are deposited after ion beam pretreatment according to gas type The surface of PTFE, a low dielectric constant polymer, was subjected to ion beam treatment using different types of gases, and then copper was evaporated onto it.
[0086] Then, to evaluate the adhesion between the PTFE substrate and the copper coating layer, the ASTM D4541 pull-off test, the cross-cut test, and the 90° peeling test were performed.
[0087] FIG. 9 is a graph showing the results of an adhesion test of a low dielectric constant polymer substrate according to an embodiment of the present invention.
[0088] FIG. 10 is an image showing a cross cut test result of a low dielectric constant polymer substrate according to an embodiment of the present invention.
[0089] Figure 9 shows the results of evaluating adhesion by performing a pull-off test according to ASTM D 4541. Referring to Figure 9, it can be seen that the adhesion between the low dielectric constant polymer substrate and the copper coating layer is highest when the surface of the PTFE substrate is treated with a hydrogen ion beam compared to when it is not treated with an ion beam and is treated with an argon or oxygen ion beam.
[0090] Figure 10 shows the results of evaluating adhesion by performing a cross-cut test using tesa#7475. Referring to Figure 10, it can be seen that when the surface of the PTFE substrate was not ion beam treated, and when it was treated with argon or oxygen ion beam, a large amount of the copper coating layer peeled off. On the other hand, it can be seen that when the surface of the PTFE substrate was treated with hydrogen ion beam, and when it was treated with hydrogen ion beam after argon ion beam treatment, the copper coating layer was hardly peeled off at all.
[0091] FIG. 11 is a diagram illustrating a 90° peeling test method for a low dielectric constant polymer substrate according to an embodiment of the present invention.
[0092] FIG. 12 is an image showing a result of a 90° peeling test of a low dielectric constant polymer substrate according to an embodiment of the present invention.
[0093] A 300 nm thick copper layer was sputter coated on the PTFE substrate that had been surface-modified by hydrogen ion beam pretreatment and the PTFE substrate that had not been ion beam treated. Then, to evaluate the adhesion between the PTFE substrate and the copper coating layer, copper was electrolytically plated to a thickness of 10 μm, and a 90° peeling test was performed.
[0094] 12, the adhesive strength between the PTFE substrate and the copper coating layer that was not pretreated with an ion beam was 0.1 N / cm or less, which was almost impossible to evaluate. On the other hand, the adhesive strength between the PTFE substrate and the copper coating layer that was pretreated with a hydrogen ion beam was 7 N / cm, which was significantly higher than that without ion beam pretreatment and was even higher than that with argon ion beam pretreatment.
[0095] Therefore, it was confirmed that forming a coating layer after hydrogen ion beam treatment on a low dielectric constant polymer substrate can improve the adhesion between the polymer layer and the coating layer, and that forming a coating layer after sequentially treating the low dielectric constant polymer substrate with an argon ion beam and a hydrogen ion beam can further improve the adhesion between the polymer layer and the coating layer.
[0096] While one embodiment of the present invention has been described above, a person having ordinary knowledge in the art can modify and change the present invention in various ways by adding, changing, deleting or adding elements, without departing from the spirit of the present invention as described in the claims, and this can also be said to be within the scope of the rights of the present invention. [Explanation of symbols]
[0097] 10: Low dielectric constant polymer layer 12: Surface modification layer 20: Coating layer
Claims
1. a low dielectric constant polymer layer; A surface modification layer formed on the surface of the polymer layer by pre-treatment with an ion beam; and and optionally a metal or ceramic coating layer formed on the surface modification layer; A low dielectric constant polymer substrate, characterized in that the contact angle of the surface modification layer with water is 90° or less.
2. Polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP).
2. The low dielectric constant polymer substrate according to claim 1, comprising at least one of the following:
3. 2. The low dielectric constant polymer substrate according to claim 1, wherein the low dielectric constant polymer layer has a dielectric constant of 4 or less.
4. The low dielectric constant polymer substrate according to claim 1 , wherein the low dielectric constant polymer layer has a thickness of 0.01 mm or more and less than 2 mm.
5. 2. The low dielectric constant polymer substrate according to claim 1, wherein the ion beam pretreatment is an ion beam pretreatment using hydrogen gas, helium gas, or argon gas and hydrogen gas.
6. 2. The low dielectric constant polymer substrate according to claim 1, wherein the metal is at least one of Cu, Ni, Cr and Ti.
7. 2. The low dielectric constant polymer substrate according to claim 1, wherein the ceramic is at least one of ZnO and ITO (Indium Tin Oxide).
8. An article comprising the low dielectric constant polymer substrate according to any one of claims 1 to 7.
9. The method includes the steps of: pretreating a surface of a low dielectric constant polymer layer with an ion beam for surface modification; and selectively forming a metal or ceramic coating layer on the polymer layer; The ion beam energy during the ion beam pretreatment is 50 to 2000 eV.
10. The low dielectric constant polymer layer may be made of polytetrafluoroethylene (PTFE), perfluoroalkoxy (PFA), ethylene tetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), polyvinylidene fluoride (PVDF), modified polyimide (MPI), polyphenylene sulfide (PPS), olefin, and liquid crystal polymer (LCP). The method for producing a low dielectric constant polymer substrate according to claim 9, further comprising the step of:
11. 10. The method for producing a low dielectric constant polymer substrate according to claim 9, wherein the gas used for the ion beam pretreatment is hydrogen gas, helium gas, or argon gas and hydrogen gas.
12. 10. The method for manufacturing a low dielectric constant polymer substrate according to claim 9, wherein when the gas used in the ion beam pretreatment is hydrogen, the applied power per ion beam velocity is 2 kW / mpm or less.
13. 10. The method for producing a low dielectric constant polymer substrate according to claim 9, wherein when the thickness of the low dielectric constant polymer layer is 0.01 mm or more and less than 2 mm, the applied voltage during the ion beam pretreatment is 0.5 kV or more and less than 2 kV.
14. 10. The method of claim 9, wherein the metal or ceramic coating layer is formed by sputtering deposition or ion beam assisted sputtering deposition.
15. 10. The method of claim 9, wherein the steps are performed by a roll-to-roll process.
16. 16. The method for manufacturing a low dielectric constant polymer substrate according to claim 15, wherein the process speed of the roll-to-roll process is 0.1 to 10 mpm.
Citation Information
Patent Citations
Surface-modifying device and formation of thin film on surface of organic substance and thin film-formed product
JP1997003220A
Surface modification method and surface coating method of article composed of liquid crystalline polymer material
JP2008308616A
Laminated body and flexible wiring board using it
JP2009166406A
Resin surface hydrophilization method, plasma processing device, laminate, and method for manufacturing laminate
JP2021028964A
